STRENGTHENING ISLAMIC PHILANTHROPY THROUGH NEW PRODUCTIVE WAQF MOVEMENT IN INDONESIA: Case studies in Waqf Pro 99 Sinergy Foundation - Rachim, Hadiyanto Abd; Tahir, Rusdin (Universitas Padjadjaran, 2025)
In Indonesia, Islamic philanthropy is currently underutilized. Many studies show that, if the Productive Waqf Movement is well developed, it can strengthen community resilience, particularly during the Covid-19 pandemic crisis. This sociological research aims to explore the social practice scheme of productive waqf-based culinary business during the Covid-19 pandemic located at Ampera Restaurant, Haii Coffee Shop, and Cuankie and Batagor Serayu in collaboration with Waqf Pro 99 Sinergi Foundation. This research was carried out through qualitative methods with purposively selected informants, including the CEO of Waqf Pro 99 Sinergi Foundation, managers, and employees of the culinary business. Data collection techniques through observation, interviews, literature studies, and documentation. Meanwhile, descriptive analysis with a sociological approach to development and religion reveals the phenomenon of productive Waqf in the Islamic frame. The results showed the complexity of the culinary business social practice scheme within the framework of the Faith-Based Organization, where the culinary business is a new institutional trend in the parameters of social practice. So that this study also produces several strategies for strengthening the economic activity of the culinary business through productive waqf management.